"Compassion for the Weak": Juvenile Offenders in the Qing Dynasty Legal System*. (July 2018) - Fenghua, Jing
When children committed homicide during the Qing dynasty, their cases were handled by the same justice system used for adult offenders. But from a very early time, Chinese law endorsed the notion that children and other vulnerable groups were worthy of the law's compassion. This article explores legal avenues to that compassion, from the law's efforts to clarify and define what marked a perpetrator as "weak" to the various legal provisions permitting such "weak" offenders to memorialize for mercy or request reduction and redemption of punishment. It finds that compassion for the weak was woven into both the letter of the law and the law in practice, resulting in a justice system that balanced the needs of victims and offenders alike.